ANALISIS NILAI PANCA SATYA DALAM GEGURITAN JAYAPRANA SERTA RELEVANSINYA TERHADAP PENGUATAN KARAKTER SISWA KELAS X DI SMK NEGERI 1 BUSUNGBIU - Purnamiasih, Dewa Ayu Komang Sri; Made Susila Putra; Made Reland Udayana Tangkas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the values of Panca Satya in Geguritan Jayaprana by I Ketut Ginarsa and to examine their relevance to strengthening the character of tenth-grade students at SMK Negeri 1 Busungbiu. The study is motivated by the gap between students' weak internalization of character values, such as discipline violations, and the demands of professional character in the workplace, as well as the limited research linking Balinese local wisdom to character education in vocational schools. This research employs a descriptive-interpretative qualitative method that combines textual analysis with field-based contextual study. The text of Geguritan Jayaprana was analyzed using Riffaterre's semiotics to identify and interpret the values of Panca Satya, which were then classified according to Max Scheler's hierarchy of values. Field data obtained through observation, interviews, and documentation at SMK Negeri 1 Busungbiu were analyzed using Thomas Lickona's character education theory, with data validity examined through source triangulation. The findings show that Geguritan Jayaprana contains five dimensions of Panca Satya values, namely Satya Hredaya, Satya Wacana, Satya Laksana, Satya Semaya, and Satya Mitra, with Satya Semaya as the most dominant matrix. Based on Max Scheler's hierarchy, Satya Hredaya occupies the value of holiness, Satya Wacana, Satya Laksana, and Satya Semaya occupy spiritual values, while Satya Mitra occupies vital values. All five values proved relevant to strengthening students' honesty, politeness, discipline, responsibility, commitment, and social care, although students' moral feeling and consistent moral action still need to be strengthened beyond mere moral knowing. This study recommends the use of Geguritan Jayaprana as a source of character education based on Balinese local wisdom in schools. Keywords: Panca Satya, Geguritan Jayaprana, Riffaterre's semiotics, Max Scheler's values, character education, SMK Negeri 1 Busungbiu.